Pengaruh Variasi Parameter Proses Pembubutan Poros untuk Menghasilkan Kondisi Pemotongan Ekonomik dan Kondisi Pemotongan Produktif - Sunardi, Edo; Lubis , Sobron Yamin; Rosehan , Rosehan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This study aims to find out how to determine the optimal shaft turning process parameters to produce minimum production costs and maximum production quantities, then to determine the optimal shaft turning process parameter values to produce minimum production costs and maximum production quantities in this study. In this study, an experimental research method was used which began with making working drawings of the shaft up to the turning process. Based on the results of the test data obtained, it shows that , the conclusions obtained include: The greater the value of the cutting speed used, the machining time will shorten. This can be proven by an example using the same feed, namely 0.25 mm/r. The greater the value of the feed used, the machining time will be shortened. This can be proven by an example using the same cutting speed of 180 m/min. In the use of the parameter roughing cutting speed of 180 m/min and finishing cutting speed of 251 m/min. The greater the value of the cutting speed used, the lower the surface roughness value.